2000
DOI: 10.1016/s0034-5687(99)00100-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and respiratory reflexes in the tropical fish, traira (Hoplias malabaricus): CO2/pH chemoresponses

Abstract: To examine the distribution and physiological role of CO 2 /pH-sensitive chemoreceptors in the gills of the tropical fish, traira (Hoplias malabaricus), fish were exposed to acute environmental hypercarbia (1.25, 2.5 and 5.0% CO 2 in air) and subjected to injections of HCl into the ventral aorta and buccal cavity. This was done before and after selective denervation of branchial branches of the IXth and Xth cranial nerves to various gills arches. Hypercarbia produced a significant decrease in heart rate, a mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 26 publications
5
37
1
2
Order By: Relevance
“…However, the progressive denervation had no significant effect on any of the respiratory variables, suggesting that there is no significant sensory input arising from the gills under normoxic, normocarbic conditions modulating respiratory drive. Similar observations have been made by others on other species (Sundin et al, 1999;Reid et al, 2000). …”
supporting
confidence: 92%
See 1 more Smart Citation
“…However, the progressive denervation had no significant effect on any of the respiratory variables, suggesting that there is no significant sensory input arising from the gills under normoxic, normocarbic conditions modulating respiratory drive. Similar observations have been made by others on other species (Sundin et al, 1999;Reid et al, 2000). …”
supporting
confidence: 92%
“…traíra (Gilmour and Perry, 1996;Reid et al, 2000;Sundin et al, 2000;. They also had no effect in jeju in the present study.…”
supporting
confidence: 45%
“…Typically, most species that have been examined exhibit hyperventilation that is mediated by increases in breathing frequency and/or ventilatory stroke volume (Dejours, 1973;Janssen and Randall, 1975;Randall et al, 1976;Smatresk and Cameron, 1982;Perry and Gilmour, 1996;Crocker et al, 2000;Perry et al, 2009b) (for reviews, see Shelton et al, 1986;Perry and Wood, 1989;Milsom, 1995;Gilmour, 2001;Perry and Gilmour, 2002;Gilmour and Perry, 2007;Perry et al, 2009a;Perry and Abdallah, 2012). The cardiovascular responses to hypercapnia have received less attention but in those few species that have been examined, a conserved response appears to be bradycardia Sundin et al, 2000;Reid et al, 2000;Perry and McKendry, 2001;Gilmour et al, 2005) which may, or may not, be associated with an increase in arterial blood pressure (reviewed by Gilmour and Perry, 2007). Bradycardia, however, is not a universal response to hypercapnia; two species were shown to exhibit tachycardia [Acipenser transmontanus (Crocker et al, 2000) and Tinca tinca (Randall and Shelton, 1963)] and in others, cardiac frequency is unaltered (Gilmour and Perry, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The tambaqui is a hypoxia-tolerant (P 50 =2.4·mmHg; Brauner et al, 2001) and hypercarbia-tolerant neotropical fish species that is found throughout the Amazon basin, often in floodplain lakes that are subject to large variations in O 2 , CO 2 and pH. Owing to the frequent occurrence of hypercarbic conditions in its natural environment (water total dissolved CO 2 may range from 0.82 to 1.79·mmol·l -1 depending on season and depth; Reid et al, 2000), and an anatomy that renders this species amenable to surgical sectioning of nerves innervating selected chemosensory areas, the tambaqui has been the focus of a concerted research effort to identify the locations and roles of chemoreceptors involved in respiratory reflexes to both hypoxia and hypercarbia Milsom et al, 2002;Reid et al, 2003;Florindo et al, 2004). Previous studies have focused primarily on reflex changes in ventilation and heart rate during hypoxic or hypercarbic exposures without monitoring blood gas or acid-base status.…”
mentioning
confidence: 99%